A new species of Lasioseius (Acari: Blattisociidae) from Brazil with morphological and DNA barcode data - Merlin, Bruna L.; Castilho, Raphael C.; de Moraes, Gilberto J. (Zootaxa, 2021)
Lasioseius foliatisetus n. sp. is described based on the morphology and molecular markers of adult females collected in litter/soil samples of the Caatinga and Pantanal, extensive Brazilian biomes. This new species can be distinguished from other Lasioseius species mainly by having fixed cheliceral digit with three teeth in addition to apical tooth, most dorsal shield setae leaf-shaped, and ventrianal shield with seven pairs of setae (including Jv5) in addition to the circumanal setae. The determined nucleotide sequences of the CytB gene and of ITSS of Lasioseius foliatisetus n. sp. are the first data of these types deposited in a published database (GenBank) for a species of this genus. The phylogenetic tree generated in the analysis of ITSS sequences showed a clade constituted only by species of the superfamily Phytoseoidea, including L. foliatisetus n. sp.. The phylogenetic tree generated in the ML analysis based on CytB showed a separation of the blattisociid species (including L. foliatisetus n. sp.) in one clade and the phytoseiid species in another clade. The analysis of the 28S 1–3 domain by itself did not allow the separation of the new species here described from species of other blattisociid genera.